Compulsion an Alex Delaware novel - Kellerman, Jonathan (Ballantine Books, 2008)
LAPD detective Milo Sturgis and psychologist Alex Delaware must solve a series of murders involving the use of expensive black automobiles at the scene of the crimes. And what does a child missing for sixteen years have to do with their search for the perpetrator?